2006
DOI: 10.1186/1465-9921-7-141
|View full text |Cite
|
Sign up to set email alerts
|

Onset of relief of dyspnoea with budesonide/formoterol or salbutamol following methacholine-induced severe bronchoconstriction in adults with asthma: a double-blind, placebo-controlled study

Abstract: Background: The long-acting β 2 -agonist (LABA) formoterol has an onset of effect comparable to that of salbutamol. Consequently, the combination of formoterol and budesonide in one inhaler, approved for maintenance use, can potentially be used for reliever therapy. This study compared the onset of relief from induced bronchospasm with a single dose of budesonide/formoterol versus standard salbutamol therapy in patients with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 29 publications
0
7
0
2
Order By: Relevance
“…In the two investigational studies found using these search criteria [Jonkers et al 2006;Green et al 1996] it would appear that both salbutamol, administered via either a DPI or pMDI, and formoterol, administered via Turbuhaler, are effective and fast acting when bronchoconstriction is induced by methacholine challenge. These findings support those clinical studies examining the effects of bronchodilators administered via DPI in an ED.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the two investigational studies found using these search criteria [Jonkers et al 2006;Green et al 1996] it would appear that both salbutamol, administered via either a DPI or pMDI, and formoterol, administered via Turbuhaler, are effective and fast acting when bronchoconstriction is induced by methacholine challenge. These findings support those clinical studies examining the effects of bronchodilators administered via DPI in an ED.…”
Section: Resultsmentioning
confidence: 99%
“…In the acute asthma setting, eight studies were double-blind, randomised studies (six in adults [Balanag et al 2006;Rubinfeld et al 2006;Boonsawat et al 2003;Phanareth and Laursen, 1999;Nana et al 1998;Grunfeld et al 1996] and two in children [Drblik et al 2003;Springer et al 1996]), two were open-label studies (one in adults [Cordova and Accinelli, 2004] and one in children [Sole et al 1995]), and two were investigational studies (methacholine challenge) [Green et al 1996;Jonkers et al 2006]. For the acute COPD studies, one was double-blind randomised [van den Broek et al 2008], one was single-blind and randomised [Cazzola et al 2002] and one was open-label [Cazzola et al 2003].…”
Section: Resultsmentioning
confidence: 99%
“…The short-and long-term effects of a range of treatments on actual and perceived bronchoconstriction and dyspnea have been studied, including SABAs, long-acting b 2 -agonists (LABAs), ICSs, and ICS-LABA combinations. [35][36][37][38][39] Recovery after methacholine-induced bronchoconstriction is often used as an experimental model to assess perception of bronchodilatation. In a study of changes in VAS-rated symptoms and FEV 1 after inhalation of 5 consecutive increasing doses of terbutaline (cumulative dose, 800 mg), the strongest correlations with subjective VAS-rated symptoms were with specific inspiratory resistance and FEV 1 .…”
Section: Medication Effectsmentioning
confidence: 99%
“…Результаты ряда исследований показали идентичность ЭМД ФК БДП/ФОР и ФК будесонид (БУД)/ФОР в отношении прироста объема форсированного выдоха за 1-ю секунду (ОФВ 1 ), а также преимущество ЭМД ФК БДП/ФОР, применяемой в режиме MART, по сравнению с традиционной терапией ЭМД ФК БДП/ФОР и сальбутамолом по требованию, показавшие регресс симптомов астмы и сокращение тяжелых обострений [11,12]. Эффект снижения риска развития первого тяжелого обострения у больных БА на фоне лечения в соответствии с концепцией MART по сравнению с традиционной терапией сопровождался достоверной положительной динамикой вторичных показателей (снижением частоты тяжелых обострений, назначения системных стероидов и обращений за экстренной медицинской помощью или госпитализаций) [13].…”
unclassified